A Sociological Approach to Childhood in the Icelandic Sagas - Katherine Vasquez 1992- (2019)
The few scenes that include children as social actors in Old Norse documentation display little explicit representation of childhood in the Medieval North. Instances of intergenerational interaction, such as Egill Skalagrimsson’s volatile relationship with his father as a potential prefiguration of his adulthood character, seem to dip more into the realm of psychology, rather than historical literature analysis. As such, it is the burden of scholars to untangle what we do have using the type of research and analysis perhaps a bit out of range for the general medieval Scandinavian academic. My primary interest with respect to this topic is the depiction of childhood in medieval Icelandic narratives, and how the children in these stories can be analyzed using approaches in other disciplines within the social science array. As such, I use an interdisciplinary approach to analysis in accordance with representations of children in the various Sagas of Icelanders, which are understood as a later medieval interpretation of oral, Viking Age Icelandic narratives. To begin, I explore the sociological theory of childhood as a “social construction,” rather than an inherent and standardized feature in all societies. Through these theories I analyzed how narrative helps to maintain the social construction of childhood in societies, pulling largely from Margaret Somers’ work on narrative and identity. With these works and concepts as a foundation, I then examined occurrences of children in the Sagas of Icelanders, such as the childhoods of Egill Skallagrimsson and Grettir Ásmundarson, with the objective of shedding light on the intentions and expectations of childhood in early medieval Iceland. Fornnorrænar heimildir eru fáorðar um bernsku á miðöldum. Þegar sagt er frá samskiptum kynslóðanna, t.d. eldfimu sambandi feðganna Egils og Skalla-Gríms, þá virðist fremur skírskotað til sálarfræði en sagnfræði. Til að vinna úr þeim heimildum sem við höfum, má líka styðjast við nálganir og greiningaraðferðir sem miðaldafræðingar á ...